Design and Rationale of the Home Blood Pressure Telemonitoring Linked with Community Health Workers to Improve Blood Pressure (LINKED-BP) Program. (15th April 2023) - Commodore-Mensah, Yvonne; Liu, Xiaoyue; Ogungbe, Oluwabunmi; Ibe, Chidinma; Amihere, Johnitta; Mensa, Margaret; Martin, Seth S; Crews, Deidra; Carson, Kathryn A; Cooper, Lisa A; Himmelfarb, Cheryl R
Abstract: BACKGROUND: Disparities in hypertension outcomes persist among Black and Hispanic adults and persons living in poverty in the United States. The "LINKED-BP Program" is a multi-level intervention linking home blood pressure (BP) monitoring with a mobile health application, support from community health workers (CHWs), and BP measurement training at primary care practices to improve BP. This study is part of the American Heart Association RESTORE (AddRE ssing S ocial Determinants TO pR event hypE rtension) Network. This study aims to examine the effect of the LINKED-BP Program on BP reduction and to evaluate the reach, adoption, sustainability, and cost-effectiveness of the intervention. METHODS: Using a hybrid type I effectiveness-implementation design, 600 adults who have elevated BP or untreated stage 1 hypertension without diabetes, chronic kidney disease, history of cardiovascular disease (stroke or coronary heart disease) and age < 65 years will be recruited from 20 primary care practices including community health centers in the Maryland area. The practices are randomly assigned to the intervention or the enhanced usual care arms. Patients in the LINKED-BP Program receive training on home BP monitoring, BP telemonitoring through the Sphygmo app, and CHW telehealth visits for education and counseling on lifestyle modification over 12 months. The primary clinical outcome is change from baseline in systolic BP at 6 and 12 months. DISCUSSIONS: The LINKED-BP Program tests a sustainable, scalable approach to prevent hypertension and advance health equity. The findings will inform implementation strategies that address social determinants of health and barriers to hypertension prevention in underserved populations. ClinicalTrials.gov IDENTIFIER: NCT05180045. Graphical Abstract: